ADDITION OF MANGOSTEEN RIND (Garcinia mangostana L.) SIMPLICIA IN FEED ON DIFFERENTIATION OF LEUKOCYTES OF AFRICAN CATFISH (Clarias gariepinus) INFECTED BY Aeromonas hydrophila - Syatma, Mario; Lukistyowati, Iesje; Aryani, Netti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on 12nd May until 23rd July 2015. The aims of thisresearch was to determine the best dose of mangosteen rind (Garcinia mangostanaL.) simplicia addition in feed to increase non-specific immune responses in Africancatfish (Clarias gariepinus). This research used Completely Randomized Design(CRD) with one factor, five treatments and three replications. The treatments wereaddition of mangosteen rind simplicia in feed with different concentration i.e : Kn(without addition of mangosteen rind simplicia and without infected with A.hydrophila), Kp (without addition of mangosteen rind simplicia and infected with A.hydrophila), P1 (addition of mangosteen rind simplicia 2 g/kg of feed and infectedwith A. hydrophila), P2 (addition addition of mangosteen rind simplicia 4 g/kg of feedand infected with A. hydrophila) and P3 (addition of mangosteen rind simplicia 6 g/kgof feed and infected with A. hydrophila). The results showed that mangosteen rindsimplicia in feed of treatment P3 on the best dose (6 g/kg of feed) and it can beincrease of non-specific immune responses in African catfish.Key words : Garcinia mangostana L., Clarias gariepinus, A. hydrophila,Simplicia, Differentiation of Leukocytes